Some characteristics of the resultant air flow from motions induced by ventilation and heat source in a two-dimensional enclosure - Tran, T. V.; Thuy, N. T. (Vietnam Journal of Mechanics, 2015)
Ventilated air flow in an enclosure is often unsteady (turbulent) at even very low Reynolds number (Re). Meantime natural convection in a box is stationary motion at large enough Rayleigh number (Ra). This paper deals with the interaction between two those flows in a two-dimensional room. The room has one inlet and one or two outlets. A heat source locates on the floor. The numerical simulation of the interaction is carried out at some values of Re and Ra for two cases of the inlet and outlet configuration. Some interesting characteristics of the resultant flow are discovered. The heat amount released by the source and removed from the room by different types of this flow is also provided.